Biogas Production from Tofu Industrial Wastewater with Effective Microorganisms 4 (EM-4) as Biocatalyst - Mohamad Rusdi Hidayat (Balai Riset dan Standardisasi Industri Pontianak, 2012)
The addition of Effective Microorganims 4 (EM-4) activator against the biogas production was done to utilize the tofu industrial wastewater as one of the substrate for biogas production so it can increase its economic value. The aim of this research was to determine the optimum EM-4 concentration as a biogas activator using tofu industrial wastewater as a substrate. This research was conducted by adding the EM-4 activator with different concentrations of 0.25%, 0.50%, 0.75%, and 1% into the 20 litre of tofu wastewater substrate. The process of biogas formation was observed through a pressure reading on pressure gauge tools on digester. The burning of biogas is done after the presure became constant. The optimal EM-4 activator addition for 20 litre of tofu wastewater substrate was 0.75%, with burning time is 14 minutes 56 seconds.